Disease-Associated Mutations Prevent GPR56-Collagen III Interaction - Luo, Rong; Jin, Zhaohui; Deng, Yiyu; Strokes, Natalie; Piao, Xianhua (PLOS ONE, 2012)
GPR56 is a member of the adhesion G protein-coupled receptor (GPCR) family. Mutations in GPR56 cause a devastating human brain malformation called bilateral frontoparietal polymicrogyria (BFPP). Using the N-terminal fragment of GPR56 (GPR56N) as a probe, we have recently demonstrated that collagen III is the ligand of GPR56 in the developing brain. In this report, we discover a new functional domain in GPR56N, the ligand binding domain. This domain contains four disease-associated mutations and two N-glycosylation sites. Our study reveals that although glycosylation is not required for ligand binding, each of the four disease-associated mutations completely abolish the ligand binding ability of GPR56. Our data indicates that these four single missense mutations cause BFPP mostly by abolishing the ability of GPR56 to bind to its ligand, collagen III, in addition to affecting GPR56 protein surface expression as previously shown.